Students’ Responses toward the Use of Quizizz in English Class - Rizkariani Sulaiman; Muhammad Affan Ramadhana (Didaktika: Jurnal Kependidikan, 2022)
This research is aimed at knowing students perception toward Quizizz as English learning media as that Quizizz is an educational app that enables students to participate in fun multiplayer class acitivties. This research applied descriptive quantitative method. It was conducted by lesson study platform. The research was conducted at SMPN 23 Makassar. The research participant was 38 students at eight grade first semester 2021/2022. The instrument of the research was questionnaire. Classically students have positive statements of the usage of Quizizz as the learning media for English learning as the shake of its interesting and fun features and impressions, the chance in peer learning to solve some challenging and step by step questions in form of Quiz. Beside that, Quizizz application enable the teachers to handle hybrid learning by effective students engagement. As the suggestion, before applying Quizizz as learning media, the students have to get used to use this application to minimize constraint usage during teaching learning process.